Development of a fiber optic high-precision position sensor - Ruan, Fang. (2008)
Fiber optic displacement sensors have been studied since 1970s. While progress has been made and many sensor types have been demonstrated, the technology is not yet fully developed nor exploited. Practical problems remain in the areas of improving the detection process, stability and resolution, optimising construction and packaging. In this project, two kinds of all fiber optic interferometric position sensors are proposed, constructed and characterised. One is a single arm Michelson interferometer, which produces a signal sensitive to displacement while insensitive to environmental perturbations; the other is based on Sagnac interferometer where the sensor output is not directly related to the displacement but to the velocity of a moving object, with the object position obtained by velocity integration. While the previous one uses a minimum of optical components and requires a minimum of optical adjustments, the latter one has potentially wider applications.